Empirical analysis of the role of new energy transition in promoting china’s economy - Liu, Xiaofei; Li, Jingcheng; Han, Lina; Zhou, Biao (Frontiers in Environmental Science, 2022)
In order to accelerate the development of new energy industry and social economy, this paper presents an empirical analysis of the role of new energy transformation in promoting China’s economy. On the basis of analyzing the concept and types of new energy, the necessity of transformation and upgrading of new energy industry is discussed. The new energy consumption data from 2010 to 2020 and China’s GDP data are selected as the basic data, and the MS-VAR model is used as the base model for the empirical analysis. The model combines the Markov zone transition model and the autoregressive model, which is suitable for analyzing non-linear problems. The results of the empirical analysis show that the new energy transition is an important way to promote new energy consumption, and it plays a role in promoting the balanced development of China’s economic growth. Combining the results of the empirical analysis, this paper gives suggestions related to the new energy transition from the institutional, economic and technological perspectives.